High impedance fault localization in a distribution network using the discrete wavelet transform - Ali, M.S.; Abu Bakar, A.H.; Mokhlis, Hazlie; Arof, Hamzah; Illias, Hazlee Azil; Aman, M.M. (2012)
Basic guidelines for the preparation of a technical work for the Locating the faulty section for High Impedance Fault (HIF) in a power system is a major challenge especially for a radial distribution network. This is due to the effect of the complexity of the distribution network such as branches; non-homogenous lines and high impedance fault that results in a variation of fault location. In this paper, analysis of fault location using the discrete wavelet transform based Multi-Resolution Analysis (MRA) and database approach is proposed. The three-phase voltage signal at the main substation to be analyzed was measured. The 1 st, 2 nd and 3 rd level of detail coefficients were extracted for each phase and were used for the identification of faulty section using the proposed method. The simulation on a 38 nodes distribution network system in a national grid in Malaysia using PSCAD software was simulated. The proposed method has successfully determined the faulty section.